The CX3CL1/CX3CR1 reprograms glucose metabolism through HIF‐1 pathway in pancreatic adenocarcinoma. Issue 11 (13th September 2013) - Ren, He; Zhao, Tiansuo; Sun, Junwei; Wang, Xiuchao; Liu, Jingcheng; Gao, Song; Yu, Ming; Hao, Jihui
ABSTRACT One of the hallmarks of cancer is revised glucose metabolism that promotes cell survival and proliferation. In pancreatic cancer, the regulatory mechanism of glucose metabolism remains to be elucidated. In this study, we found that CX3CR1 is expressed in pancreatic cancer cells lines. Exogenous or transfected CX3CL1 increased glucose uptake and lactate secretion. CX3CL1 stimulated HIF‐1 expression through PI3K/Akt and MAPK pathways. Furthermore, knockdown of HIF‐1 blocked CX3CL1‐modified glucose metabolism in pancreatic adenocarcinoma cells. In conclusion, the CX3CL1/CX3CR1 reprograms glucose metabolism through HIF‐1 pathway in pancreatic cancer cells. J. Cell. Biochem. 114: 2603–2611, 2013. © 2013 Wiley Periodicals, Inc.